Parkinson Disease - Intan Sahara Zein; Khairunnisa Khairunnisa (Pusat riset dan Inovasi Nasional, 2023)
Parkinson's disease is a disorder of brain function caused by the process of degeneration of the basal ganglia in the substantia nigra pars compacta (SNc) cells and is characterized by characteristics such as tremor at rest, rigidity of muscles and joints (rigidity), slowness of movement and speech (bradykinesia) and instability upright position (postural instability). Parkinson's Disease occurs in the range between the ages of 55 to 65 years and occurs in 1% -2% of people over the age of 60 years, increasing to 3.5% at the age of 85-89 years. Approximately 0.3% of the general population, the prevalence is higher in males than females with a ratio of 1.5:1.0. Manifestations that can be found in patients with Parkinson's Disease can be assessed through the Hoehn and Yahr Scale (HY). Current treatment for Parkinson's disease aims to reduce motor symptoms and slow the progression of the disease.